Impact of sex on uric acid levels and its relationship with the extent of coronary artery disease: A single-centre study. Issue 1 (July 2015) - Barbieri, Lucia; Verdoia, Monica; Schaffer, Alon; Marino, Paolo; Suryapranata, Harry; De Luca, Giuseppe; ,
Abstract: Background: Serum uric acid (SUA) elevation has been largely addressed in the past as a possible risk factor for cardiovascular disease. However, uric acid has not clearly emerged as independent risk factor for coronary artery disease. Several studies in literature have assessed sex-related differences in the association between elevated SUA levels and cardiovascular events with conflicting results. Therefore, aim of the current study was to evaluate the relationship between uric acid levels and the extent of coronary artery disease in male and female patients undergoing coronary angiography. Methods: Our population is represented by 3520 consecutive patients undergoing coronary angiography from March 2007 to October 2012. Patients were divided according to Tertiles of SUA (Males, Group 1, ≤5.5 mg/dL–0.33 mmol/mol, n = 762, Group 2, 5.5–6.8 mg/dL–0.33–0.40 mmol/mol, n = 829 and Group 3 ≥6.8 mg/dL–0.40 mmol/mol, n = 851), (Females, Group 1, ≤4.8 mg/dL–0.28 mmol/mol, n = 349, Group 2, 4.8–6.3 mg/dL–0.28–0.37 mmol/mol, n = 359 and Group 3 ≥ 6.3 mg/dL–0.37 mmol/mol, n = 370). Fasting samples were collected for uric acid levels assessment. Coronary disease was defined for at least 1 vessel stenosis >50% as evaluated by QCA. Severe coronary disease was defined as three-vessel disease and/or left main disease. Results: Among 3520 patients, we identified 2442 men (69.4%) and 1078 women (30.6%). Males had higher levels of uric acid than women (6.33 ± 1.7 vs 5.8 ± 1.9 – p < 0.001). The association between elevated uric acid (≥7 mg/dl or 0.42 mmol/l) and male gender was confirmed after correction for baseline confounding factors (Adjusted OR = 1.28 [1.01–1.62], p = 0.004). Males displayed a significantly higher prevalence and extent of CAD (p < 0.001) and more complex coronary lesions (p < 0.001). However, no significant relationship was observed between uric acid and CAD (Adjusted OR [95%CI] = 0.90 [0.76–1.06], p = 0.22) or severe CAD (Adjusted OR [95%CI] = 0.89 [0.79–1.01], p = 0.08). Among females, higher SUA levels were significantly associated with higher prevalence of severe CAD (p < 0.001) (Adjusted OR [95% CI] = 1.29 [1.03–1.62], p = 0.03). Conclusion: Our study showed that uric acid levels are significantly higher in men. However, high uric acid levels are associated with severe CAD only in women. Future large studies are certainly needed to confirm our findings and to evaluate the effects of SUA lowering therapies on cardiovascular prevention and outcome, especially in women. Highlights: Several studies assessed gender-related differences in the association between elevated SUA and CAD with conflicting results. Among 3520 patients we showed that males displayed a higher prevalence and extent of CAD and more complex coronary lesions. No significant relationship was observed between uric acid and CAD or severe CAD in males. Among females, higher SUA levels were significantly associated with higher prevalence of severe CAD.